NASKAH AKADEMIK, TANTANGAN DPRD KABUPATEN/KOTA DALAM PEMBENTUKAN PERATURAN DAERAH - Ibrahim Fattah (Madani Legal Review, 2019)
This study aims to find out and examine the challenges of the district / city DPRD in preparing Academic Manuscripts as the initial manuscript for planning the formation of local regulations that are extracted from the community (botton up) as a result of legal research. The type of research used is juridical-normative and juridical-empirical research. In order to realize the Academic Script in the formation of regional regulations at the district / city level, the DPRD faces challenges in terms of routine routines within the DPRD and in its parties. Academic manuscripts in the formation of regional regulations have not yet become a well-planned stage so that the rationale and reasons for the need for the preparation of academic texts as a reference for the establishment of certain regional regulations have not been revealed in a comprehensive and systematic manner. The legal basis of academic texts has been very strong, especially after the birth of Law Number 12 of 2011 concerning the Establishment of Legislation, as stated in Article 56 paragraph (2). Community participation and stakeholders in public discussion / consultation activities are spaces provided to accommodate views, proposals and include criticism of the establishment of the Regional Regulation.